Criteria for identifying potentially resectable patients with initially oncologically unresectable hepatocellular carcinoma before treatment with lenvatinib plus an anti–PD–1 antibody - Xu, Bin; Zhu, Xiao-Dong; Shen, Ying-Hao; Zhu, Jin-Jin; Liu, Jie; Li, Mei-Ling; Tang, Pei-Wen; Zhou, Jian; Fan, Jia; Sun, Hui-Chuan; Huang, Cheng (Frontiers in Immunology, 2022)
Background: Conversion therapy is feasible in patients with oncologically unresectable hepatocellular carcinoma (HCC). However, it is challenging to prospectively identify patients who are more likely to achieve successful conversion before initiating systemic therapy, either alone or combined with locoregional therapy. Methods: Criteria for identifying potentially resectable patients with initially oncologically unresectable HCC before treatment with lenvatinib plus an anti-PD-1 antibody were proposed based on real-world evidence. Multivariate Firth logistic regression was used to validate the proposed criteria in a retrospective cohort of consecutive patients with advanced HCC, who received combination therapy with lenvatinib plus an anti-PD-1 antibody between September 2018 and September 2021. Results: The proposed criteria were as follows: (1) Eastern Cooperative Oncology Group performance status of 0 or 1; (2) Child-Pugh class A; (3) intrahepatic tumors confined to one lobe (left, right, or middle lobe), or present in one lobe alongside a single tumor with diameter ≤5 cm or up to three tumors each with diameter ≤3 cm in the remaining lobes, with R0 resection achievable by hemihepatectomy, alone or combined with locoregional therapy to the remaining lobes during surgery; and (4) no portal vein tumor thrombus involving the contralateral liver lobe or reaching the superior mesenteric vein, no hepatic vein tumor thrombus involving more than two major hepatic vein branches on the tumor side, and no tumor thrombus of the inferior vena cava reaching the atrium. Firth logistic regression confirmed the criteria were an independent predictor of surgery following conversion therapy with lenvatinib plus an anti-PD-1 antibody. Conclusions: This study proposed and validated criteria for identifying patients with initially oncologically unresectable HCC who are potentially resectable when treated with combination therapy with lenvatinib plus an anti-PD-1 antibody. The proposed criteria could help standardize conversion therapy studies in advanced HCC.